PENERAPAN METODE ROLE-PLAYING UNTUK MENINGKATKAN HASIL LAYANAN INFORMASI BAGI SISWA KELAS VIII SMP - Nursanti, Kesi (Perspektif Ilmu Pendidikan, 2019)
This study aims to describe the effectivity of information service through the adaptation of the role-playing method. This research was a classroom action research which focused on the activities during counseling and guidance program within three cycles wherein each cycle has three face-to-face meetings. Observation and attitude scale were used to collect the data. This research was conducted in SMPN 62 Jakarta with a total of 36 students of class VIII as participants. The results show that student interest to participate in information service and activity in following the information service process was increased. This increase was shown by the increase in the mean score of attitude scale; the class attitude mean score in cycle two increased by 4,09% compared to the mean score in cycle one. Subsequently, the mean score in cycle three increased by 1,67% compared to cycle two. Based on these results, discussion and conclusion of this research are provided. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">